Second-trimester maternal serum screening for fetal Down syndrome: As a screening test for hemoglobin Bart's disease: A prospective population-based study - Chanane Wanapirak (2018)
© 2018 John Wiley & Sons, Ltd. Purpose: The purpose of this study is to determine the effectiveness of second-trimester maternal serum screening for Down syndrome as a screening test for fetal hemoglobin (Hb) Bart's disease among an unselected population. Methods: A secondary analysis of a large prospective database (20 254 pregnancies) was conducted to compare the levels of maternal serum screening, alpha-fetoprotein (AFP), free beta-human chorionic gonadotropin, and unconjugated estriol between pregnancies with Hb Bart's disease and unaffected pregnancies. Results: The median AFP levels were much higher among affected fetuses (1.96 vs 1.12 multiple of the median; P <.001), yielding a sensitivity of 81.6% and specificity of 86.4%. Thus, AFP measurement is effective in predicting fetal Hb Bart's disease among an unselected population when using a cutoff value of 1.5 multiple of the median. The serum free beta-human chorionic gonadotropin levels were slightly, but significantly, higher in the affected pregnancies, while the serum unconjugated estriol levels were minimally, but significantly, lower among the affected pregnancies. Conclusion: Second-trimester maternal serum AFP levels were significantly elevated in cases of fetal Hb Bart's disease. Pregnancies with unexplained elevated serum AFP levels in areas of high prevalence of Hb Bart's disease should always undergo a detailed ultrasound examination to detect any early signs of fetal anemia before development of hydrops fetalis.